PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN SARANA PRASARANA TERHADAP MUTU PENDIDIKAN DI SDIT ALMANAR KOTA BEKASI - Yuni, Sri Wahyuni; Iqbal, Muhammad; Victorynie, Irnie (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The quality of education is one of the most important goals of schools. Achieving high-quality education requires various supporting factors, including leadership style, organizational culture, and facilities and infrastructure. This study aims to analyze the influence of leadership style, organizational culture, and facilities and infrastructure on the quality of education at SDIT Al-Manar, Bekasi City. A qualitative research method with a pedagogical approach was used in this study. The primary data source comes from interviews with the principal and teachers at SDIT Al-Manar, Bekasi City. Meanwhile, secondary data were obtained from documents supporting the research results. The tool used to collect data was in-depth interviews. Observation and documentation were conducted by selecting data as a source of information, analyzing data, interpreting data, and drawing conclusions.The results of the study show that leadership style, organizational culture, and facilities and infrastructure have a positive and significant impact on the quality of education at SDIT Al-Manar, Bekasi City. Democratic and transformative governance can motivate teachers and staff to improve their performance, thereby positively affecting the quality of education. A collaborative and supportive culture can create a better learning environment for students, thus enhancing student learning. Adequate and well-maintained infrastructure can support an effective learning process, thereby improving the quality of education. Based on the research results, it is concluded that leadership style, organizational culture, and facilities and infrastructure are important factors that can influence the quality of education at SDIT Al-Manar, Bekasi City. Therefore, efforts should be made to improve the quality of leadership, organizational culture, and facilities and infrastructure at the school. Abstrak Mutu pendidikan merupakan salah satu tujuan sekolah yang paling penting. Untuk mencapai pendidikan yang bermutu diperlukan berbagai faktor pendukung antara lain gaya kepemimpinan, budaya organisasi dan sarana prasarana. Penelitian ini bertujuan untuk menganalisis pengaruh gaya kepemimpinan, budaya organisasi dan sarana prasarana terhadap mutu pendidikan di SDIT Al-Manar Kota Bekasi. Metode penelitian kualitatif dengan pendekatan pedagogi digunakan dalam penelitian ini. Sumber data yaitu data primer berasal dari wawancara dengan kepala sekolah dan guru di SDIT Al-Manar Kota Bekasi. Sedangkan data sekunder diperoleh dari dokumen pendukung hasil penelitian. Alat yang digunakan untuk mengumpulkan data adalah wawancara mendalam. Observasi dan dokumentasi dilakukan dengan cara memilih data sebagai sumber informasi, menganalisis data, menafsirkan data, dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa gaya kepemimpinan, budaya organisasi dan sarana prasarana berpengaruh positif dan signifikan terhadap mutu pendidikan di SDIT Al-Manar Kota Bekasi. Tata kelola yang demokratis dan transformatif dapat memotivasi guru dan staf untuk meningkatkan kinerja mereka sehingga berdampak positif pada kualitas pendidikan. Budaya kolaboratif dan suportif dapat menciptakan lingkungan belajar yang lebih baik bagi siswa dan dengan demikian meningkatkan pembelajaran siswa. Infrastruktur yang memadai dan terawat dapat mendukung proses pembelajaran yang efektif sehingga dapat meningkatkan kualitas pendidikan. Berdasarkan hasil penelitian disimpulkan bahwa gaya kepemimpinan, budaya organisasi dan sarana prasarana merupakan faktor penting yang dapat mempengaruhi mutu pendidikan di SDIT Al-Manar Kota Bekasi. Untuk itu perlu dilakukan kajian untuk meningkatkan kualitas kepemimpinan, budaya kepemimpinan dan sarana prasarana di sekolah